2012
DOI: 10.1128/aem.01601-12
|View full text |Cite
|
Sign up to set email alerts
|

Serine-Type Carboxypeptidase KexA of Aspergillus oryzae Has Broader Substrate Specificity than Saccharomyces cerevisiae Kex1 and Is Required for Normal Hyphal Growth and Conidiation

Abstract: dAspergillus oryzae has an ortholog of Saccharomyces cerevisiae KEX1, termed kexA. A truncated form of KexA protein showed serine-type carboxypeptidase activity and somewhat broader substrate specificity than Kex1 protease. Furthermore, our results indicated that KexA is required for normal growth of A. oryzae and that it might be involved in hyphal branching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These genes are mainly involved in amino acid metabolism, microbial metabolism in diverse environments, carbohydrate metabolism, cell growth and death, energy metabolism, lipid metabolism, xenobiotics biodegradation and metabolism, metabolism of terpenoids and polyketides, nucleotide metabolism, replication and repair, signal transduction, translation, transcription, biosynthesis of secondary metabolites, glycan biosynthesis and metabolism, transport and catabolism, and metabolism of cofactors and vitamins pathways (Additional file 4 ). Many genes whose expression was up-regulated during microcycle conidiation encode proteins that function in cell division, cell proliferation, cell wall formation, and cytoskeletal rearrangement, including a tyrosine-protein phosphatase [ 29 ], a transcriptional coactivator [ 30 ], a zinc knuckle domain protein [ 31 ], a serine-type carboxypeptidase [ 32 ], sedoheptulose-1, 7-bisphosphatase [ 33 ], a catalase [ 34 , 35 ], cytochrome P450 [ 36 ], a mannan endo-1, 6-α-mannosidase-like protein [ 37 , 38 ], an actin-associated protein [ 39 ], and a HLH transcription factor [ 40 ], suggesting that these up-regulated genes play a role in microcycle conidiation. Interestingly, members of the normal conidiation FluG pathway, including snaD , GNAT , fluG , pkaA [ 41 ], fadA [ 42 ], and gasA [ 43 ], were up-regulated during microcycle conidiation (Additional file 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…These genes are mainly involved in amino acid metabolism, microbial metabolism in diverse environments, carbohydrate metabolism, cell growth and death, energy metabolism, lipid metabolism, xenobiotics biodegradation and metabolism, metabolism of terpenoids and polyketides, nucleotide metabolism, replication and repair, signal transduction, translation, transcription, biosynthesis of secondary metabolites, glycan biosynthesis and metabolism, transport and catabolism, and metabolism of cofactors and vitamins pathways (Additional file 4 ). Many genes whose expression was up-regulated during microcycle conidiation encode proteins that function in cell division, cell proliferation, cell wall formation, and cytoskeletal rearrangement, including a tyrosine-protein phosphatase [ 29 ], a transcriptional coactivator [ 30 ], a zinc knuckle domain protein [ 31 ], a serine-type carboxypeptidase [ 32 ], sedoheptulose-1, 7-bisphosphatase [ 33 ], a catalase [ 34 , 35 ], cytochrome P450 [ 36 ], a mannan endo-1, 6-α-mannosidase-like protein [ 37 , 38 ], an actin-associated protein [ 39 ], and a HLH transcription factor [ 40 ], suggesting that these up-regulated genes play a role in microcycle conidiation. Interestingly, members of the normal conidiation FluG pathway, including snaD , GNAT , fluG , pkaA [ 41 ], fadA [ 42 ], and gasA [ 43 ], were up-regulated during microcycle conidiation (Additional file 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…We also obtained some proteins that are involved in virulence, antagonism other fungi, and defense, including serine carboxypeptidase, superoxide dismutase, disulphide isomerase, and lactonohydrolase. Some of these proteins were predicted and/or reported to function as virulence factors ( Data S1 and S2 ), such as peptidase C1 [30] , carboxypeptidase [31] , [32] , glucanosyltransferase [33] , [34] , S-adenosylmethionine synthetase [35] , peroxiredoxin [36] , chitinase 1 [37] , catalase-peroxidase [38] , and amidase [39] . These results indicated that signal peptides–containing proteins and virulence factors might be important contributors to the strong virulence seen in Fusarium-induced banana wilt.…”
Section: Discussionmentioning
confidence: 99%
“…This peptidase is widely observed in fungi, plants, and animals and has diverse biological functions [31] . In Aspergillus oryzae , this enzyme is required for normal hyphal growth, and the deletion strain formes fewer conidia on agar plates [32] . We identified two protein spots in F4 as carboxypeptidase, indicating that carboxypeptidase might be important for hyphal growth and conidiation of F. oxysporum .…”
Section: Discussionmentioning
confidence: 99%
“…AF095574). Aspergillus oryzae also has an ortholog of Kex1 termed KexA and displays a serine-type carboxypetidase activity and a broader substrate [12]. Amino acid comparison of P. pastoris and S. cerevisiae Kex1protein shows only 36% identity and 43.7% similarity [13].…”
Section: Introductionmentioning
confidence: 99%